In base 10

After writing a solution to this problem I focused on product of digits and got the following result. Also I have a challenge also for all those who found this interesting try if you can do it!

Let f10(x)f_{10}(x) be defined as the product of digits of xx when written in base 1010 for example f10(279)=2×7×9=126f_{10}(279)=2 \times 7 \times 9=126. Then, i=10n110nf(i)=45n\boxed{\sum_{i=10^{n-1}}^{10^{n}}f(i)=45^{n}}


First, we have to see the following lemma:

LEMMA : n=10q110qf(n)=45(i=10q210q1f(i))\sum_{n=10^{q-1}}^{10^{q}}f(n)=45(\sum_{i=10^{q-2}}^{10^{q-1}}f(i))


Let Sn=n=10q110qf(n)S_n=\sum_{n=10^{q-1}}^{10^{q}}f(n)

We can remove numbers from 10q110^{q-1} to 1111...1111... (qq 1s1's) as the numbers between have a 00 in them

Similarly we have to remove numbers from 2000...2000... to 2111...2111... (q1q-1 0s0's and 1 ), from 3000...3000... to 3111...3111... (q1q-1 0s0's and 1 ) and so on.

Sn=(1×1×1...×1)+(1×1×1...×2)...+(9×9×9...×9)S_n=(1\times1\times1...\times1 )+(1\times1\times1...\times2)...+(9\times9\times9...\times9)

We can take leading digits common, reducing a single digit from each number


Now we can take n=10q210q1\sum_{n=10^{q-2}}^{10^{q-1}} by include numbers like 100...01100...01 as f(100...01)=0f(100...01)=0 so it makes no change


Using the lemma we can get


If you apply it again and again

i=10n110nf(i)=(45)(45)...(i=10nn101f(i))=(45)(45)...(45)=45n\sum_{i=10^{n-1}}^{10^{n}}f(i)=(45)(45)...(\sum_{i=10^{n-n}}^{10^{1}}f(i))=(45)(45)...(45)=\boxed{45^n} Hence proved


  • I have proved this for base 1010 you can try for any other base or you may prove it for any base bb

Note by Zakir Husain
1 year, 4 months ago

No vote yet
1 vote

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link]( link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}


Sort by:

Top Newest

The problem you mentioned is super, and generalising is even more elegant. I need to try solving the problem you linked before studying this note.

Mahdi Raza - 1 year, 3 months ago

Log in to reply

I think your argument can be adapted to any base, bb. The sum would be (b(b1)2)n\left ( \frac {b(b-1)}{2} \right )^\textup{n}.

The proof could be done by induction. The base case is just the sum of the single digits so S1\mathbf{S}_{1} equals the (b1)th(b-1)th triangular number: b(b1)2\frac{b(b-1)}{2}.

Assuming Sn=(b(b1)2)n\mathbf{S}_{n}\textup{=}\left ( \frac{b(b-1)}{2} \right )^\textup{n}, then by your leading digits argument, Sn+1=1(Sn)+2(Sn)+...+(b1)(Sn)=b(b1)2(Sn)=(b(b1)2)(b(b1)2)n=(b(b1)2)n+1\mathbf{S}_{n+1}=1(\mathbf{S}_{n})+2(\mathbf{S}_{n})+...+(b-1)(\mathbf{S}_{n})=\frac{b(b-1)}{2}(\mathbf{S}_{n})=\left ( \frac{b(b-1)}{2}\right )\left ( \frac{b(b-1)}{2} \right )^\textup{n}=\left ( \frac{b(b-1)}{2} \right )^\textup{n+1}, completing the proof by induction.

Justin Travers - 1 year, 3 months ago

Log in to reply

Good efforts!

Zakir Husain - 1 year, 3 months ago

Log in to reply


Problem Loading...

Note Loading...

Set Loading...